Evaluasi Usability Aplikasi Golife berbasis Android dari Perspektif Pengguna dengan menggunakan Metode Use Questionnaire dan Pendekatan Human-Centered Design - Arinto Bagas Satyoko; Widhy Hayuhardhika Nugraha Putra; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
PT. APLIKASI KARYA ANAK BANGSA (Gojek Indonesia) with one of its products is the application of Golife professional services. Some services such as GoMassage and GoClean are very attractive to users, but there are usability issues including interfaces such as writing that is too small to disproportionate button sizes. Further research was conducted using the USE Questionnaire method and the Human-Centered Design approach, where the use of a questionnaire was needed to measure four aspects of usability namely usefulness, ease of use, ease of learning, and satisfaction. Then the Human-Centered Design approach is needed to identify users and divide into two groups of users and conduct interviews with open-ended questions that are asked to collect the problems faced by users in operating the Golife application. From the interviews gathered, several 12 usability problems faced by users were found, mainly in terms of writing size, lack of icons and descriptions, display inconsistencies, and issues related to button interactions, to be further corrected according to the problems encountered. Recommended improvements to the use of the Golife application generate a new look to increase the value of usability. The value of the results of previous uses is only 53.08% to 85.19% with a significant increase obtained from the user group aged over 40 years from 45.69% (not good enough category), to be 89.60% (very good category).